(untitled) (American Journal of Islam and Society, 1993)
There is little dispute that the Iranian revolution, the ensuing hostage crises in Tehmn and Beirut, the Salman Rushdie affair, and, finally, the Pemian Gulf war have drastically changed the image of Islam in the West. The hetoric of the most ardent Muslim activists has been accepted at face value, and Islam has been identified as a revolutionary force with an axe to grind against the West. Although the Western phobia of Islam has some justification, the West has allowed stereotypes and shibboleths to rule its judgment too easily. Explicitly, as well as implicitly, Islam is depicted in the media and even academic literature as the religion of war, vengeance, and destruction-as a force that is inimical to the orderly conduct of international relations and the progress of society and politics. Islam is viewed as hostile to democracy, minority rights, and women’s welfare. Islam as a world civilization has been reduced to Islamic fundamentalism, and even then the West has preferred to cling to political slogans rather than grapple with complex sociopolitical pmesses in undetstanding the theoretical and political challenge of Islamic movements. The radications of the simultaneous reduction of Islam to fundamentalism and the "mythologization" of fundamentalism are immediately clear. The West turned a blind eye to a brutal military coup in Algeria in 1991, believing that martial rule would be a far better option for Algeria and the West than an Islamic government in Algiers. The reaction to the crisis in the former republics of Yugoslavia has been equally perplexing, especially in the light of Serbia’s glorification of its genocidal carnage of Bosnians as "a worthy cause" that Europe will eventually appreciate. After all, the Serbs are "doing Europe a favor by ridding it of the menace of Islam." Muslims have in fact charged, and rightly so, that the West follows a different set of standards on democracy and human rights when it comes to Muslim societies. Is the Western reaction to things Islamic mere genuflection or does it reveal a more deep-seated anger and distrust of Islam? If the latter is the case, what will the consequences of such a policy be for global interests of the West? The Islamic threat: Myth or Reality? offers answers to these queries. Esposito, a leading expert on Islamic studies who has written prolifically on the relation of Islam to politics, provides a lucid examination of the roots of Muslims’ activism and the Westem response to it. He places the attitude of Islamic movements towards the West in the context of the Muslim experience ...